Spider Silk‐Inspired Conductive Hydrogels for Enhanced Toughness and Environmental Resilience via Dense Hierarchical Structuring - Seokkyoon Hong; Jiwon Lee; Taewoong Park; Jinheon Jeong; Junsang Lee; Hyeonseo Joo; Juan C. Mesa; Claudia Benito Alston; Yuhyun Ji; Sergio Ruiz Vega; Cristian Barinaga; Jonghun Yi; et al. (Advanced Science)
Abstract Conductive hydrogels, known for their biocompatibility and responsiveness to external stimuli, hold promise for biomedical applications like wearable sensors, soft robotics, and implantable electronics. However, their broader use is often constrained by limited toughness and environmental resilience, particularly under mechanical stress or extreme conditions. Inspired by the hierarchical structures of natural materials like spider silk, a strategy is developed to enhance both toughness and environmental tolerance in conductive hydrogels. By leveraging multiscale dynamics including pores, crystallization, and intermolecular interactions, a dense hierarchical structure is created that significantly improves toughness, reaching ≈90 MJ m⁻3. This hydrogel withstands temperatures from −150 to 70 °C, pressure of 12 psi, and one‐month storage under ambient conditions, while maintaining a lightweight profile of 0.25 g cm⁻3. Additionally, its tunable rheological properties allow for high‐resolution printing of desired shapes down to 220 µm, capable of supporting loads exceeding 164 kg m⁻2. This study offers a versatile framework for designing durable materials for various applications.